Role of Consumers and Home Economists in Pakistan in Promoting Sustainable Consumption - Hakeem, Rubina (Nurture, 2008)
The possible role any consumer could play in promoting sustainable consumption or development is associated with the degree of choice a consumer has and factors influencing his choice. The purpose of this paper is to review literature and data so as to assess the prospects of empowering Pakistani consumers for enhancement of their role in promoting sustainable development. Illiteracy, lack of needed information of, poor access to available information, lack of laws, poor implementation of laws emerged as the major factors limiting the potential of Pakistani consumer in parroting sustainable consumption. Development of software for translation and transformation of needed information in local languages as readable matter and as audio recordings; proliferation and networking of consumer originations; and networking and activation of home economists to promote and support sustainable consumption are the three identified strategies that could lead to enhancement of the potential of Pakistani consumer in promoting sustainable consumption.